Atmospheric science : an introductory survey - Wallace, John M. (John Michael), 1940- (International geophysics series ;, 2006)
Wallace and Hobbs' original edition of Atmospheric Science helped define the field nearly 30 years ago, and has served as the cornerstone for most university curriculums. Now students and professionals alike can use this updated classic to understand atmospheric phenomena in the context of the latest discoveries and technologies, and prepare themselves for more advanced study and real-life problem solving. Atmospheric Science, Second Edition, has been completely revamped in terms of content and appearance. It contains new chapters on atmospheric chemistry, the Earth system, climate, and the atmospheric boundary layer, as well as enhanced treatment of atmospheric dynamics, weather forecasting, radiative transfer, severe storms, and human impacts, such as global warming. The authors illustrate concepts with colorful state-of-the-art imagery and cover a vast amount of new information in the field. They have also developed several online materials for instructors who adopt the text. With its thorough coverage of the fundamentals, clear explanations, and extensive updates, Wallace & Hobbs' Atmospheric Science, Second Edition, is the essential first step in educating today's atmospheric scientists. * Full-color satellite imagery and cloud photographs illustrate principles throughout * Extensive numerical and qualitative exercises emphasize the application of basic physical principles to problems in the atmospheric sciences * Biographical footnotes summarize the lives and work of scientists mentioned in the text, and provide students with a sense of the long history of meteorology * Companion website encourages more advanced exploration of text topics: supplementary information, images, and bonus exercises.